VERBA DALAM BAHASA DAYAK BAKATIK RARA DIALEK PAUM DI KECAMATAN JAGOI BABANG KABUPATEN BENGKAYANG - Ikasari, Ninsi; Amir, Amriani; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research deals with the field of morphology, especially regarding verbs in BDBRDP in Jagoi Babang District, Bengkayang Regency. This research is motivated by the ins and outs of word structure and the effect of changes in word structure on word classes and word meanings in the Dayak Bakatik Rara language needs to be known so that what is available can be guarded and preserved until it becomes known by the wider community. This research used descriptive linguistic method with a qualitative form. The source of data in this study was the Dayak Bakatik Rara Paum Dialect Language in Jagoi Babang District in the verbs form of the Dayak Bakatik language. Data collection techniques used refer to see, interview, record and note with a data collection tools in the form of a list of basic verb forms in Indonesian, then translated into the Dayak Bakatik Rara language. Based on data analysis, there were 102 forms of BDBRDP verbs in Jagoi Babang District, Bengkayang Regency. This research successfully collected 95 verbs of BDBRDP in Jagoi Babang District that can be derived based on affixes, suffixes, and confixes. Whereas 7 BDBRDP verbs in Jagoi Babang District could not experience in decrease the verbs.Keywords: BDBRDP in Jagoi Babang District, Verbs